DETERMINATION OF THE EPIDEMIOLOGICAL ASPECTS OF AIR POLLUTION IN ISTANBUL BY UTILIZING GIS - Alkoy, Seval; Dogru, A. Ozgur; Basaraner, Melih; Sahin, Umit; Ulugtekin, Necla; Seker, Dursun Zafer (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2009)
Air pollution is one of the most important and widespread environmental and health problems, especially at highly urbanized areas. Effects of air pollution on humans depend on geographical characteristics of the urban, type of fuels used, density of the traffic, and land-use characteristics of the immediate area. Epidemiological studies revealed that air pollution higher than the accepted threshold values causes increased morbidity and mortality due to respiratory and cardiovascular diseases. This study evaluates Istanbul in terms of air Pollution by utilizing statistical methods and Geographical Information Systems (GIS). In this context, Firstly, the concentrations of sulfide dioxide (SO,) and total suspended particles (TSP) in the air were examined by using the air quality measurements of Istanbul for a 5-years period from 1994 to 1998. Subsequently, various thematic maps were created and statistical results, such as standard deviation, mean, median, minimum and maximum values, were obtained seasonally, annually, and for the overall period. As a result of this study, Bayrampasa, Sisli, and Gaziosmanpasa districts were found to be those with highest mean values of SO, for the 5-years period, and Bayrampasa also had the highest mean value of TSP for the same period. Besides, decreasing trends of SO, and TSP concentrations for the study period were observed. In addition to the results representing the current situation of the city, this study also introduced a relationship between particle type-air pollution and mortality in Istanbul.
Keywords: Epidemiology; air pollution; environmental health; GIS; thematic maps; Environmental Sciences & Ecology